Central Provident Fund : adequacy of CPF. - Hor, Yueh Lee. (2008)
In this project, we looked into CPF's role in catering to one’s housing, retirement, healthcare and education needs.We also investigated CPF members’ perceptions towards the necessity, sufficiency and importance of CPF as well as their satisfaction towards the various CPF schemes.